Hard Candy Production and Quality Parameters: A review - Ozel, Baris; Kuzu, Sena; Marangoz, Mehmet Ali; Dogdu, Sarper; Morris, Robert H.; Oztop, Mecit H. (Open research Europe, 2024)
Hard candies are sugar confections comprising mainly water and sucrose. Corn syrup, colorants and flavors are also usually added to hard candy formulations. The production of hard candy requires heating of the ingredients to very high temperatures to reduce moisture content and subsequent cooling to obtain a solid matrix. Cooling of the mixtures achieves the final, well known glassy state of the products. In this glassy state, the system is kinetically stable and molecular mobility is restricted, providing longer shelf life to hard candies. There are, however, several factors affecting the final quality and consumer acceptance of hard candies. Production methods and parameters, initial formulations as well as storage conditions all play a crucial role in the physicochemical, textural and sensory properties of hard candies. Addition of colorants and flavors also plays a vital role in the final quality. Although hard candy production is a simple process with few production stages, even small changes in the method of production and process parameters may induce substantial changes in the final product characteristics. Additionally, storage conditions such as temperature and humidity can change the product properties leading to graining and stickiness which are the two major problems for hard candies during storage. Both production and storage conditions should therefore be carefully chosen and controlled for desirable hard candy properties. This review addresses the general production methods and considers process parameters and quality parameters of hard candy products. Moreover, a comprehensive review of the related hard candy literature is also presented. The majority of hard candy reviews focus on specific methods and processes, but this review will present a more general frame on the subject.